IMPLEMENTATION OF PROBLEM-BASED LEARNING MULTIMEDIA WITH FIND AND SORT QR CODE GAMES TO IMPROVE STUDENT'S COMPUTATIONAL THINKING SKILLS - Al Husaeni, Dwi Fitria; Rahman, Eka Fitrajaya; Piantari, Erna (Universitas Trunojoyo Madura, 2023)
This study aims to evaluate the effectiveness of using and developing problem-based learning multimedia with find and sort QR code games to improve students' computational thinking (CT) skills in learning object-oriented programming using a web-based digital platform. The Research and Development (R&D) method and One-Group Pretest-Posttest design was used in this study. The subjects of this study were 35 students of SMK Negeri 1 Cimahi, Indonesia. There are three stages in conducting research 1) analysis of problems, 2) learning multimedia development, and 3) evaluation. The findings show there is an increase in students' CT skills after implementing the find and sort QR Code Game problem-based learning multimedia during the learning process. Student learning outcomes have increased from 45.71 (pretest) to 89.50 (posttest). The average increase in student learning outcomes occurred significantly based on the results of the t-test. In addition, the students' CT average score increased from 65.43 (pretest) to 85.29 (posttest). The order of increasing the CT component based on the n-gain value is 1) abstraction (0.66); 2) pattern recognition (0.63); 3) decomposition (0.48); and 4) algorithm design (0.39). Student responses to multimedia learning in this study were obtained very well with a score of 84.95%.